2021
DOI: 10.1186/s13244-021-01017-2
|View full text |Cite
|
Sign up to set email alerts
|

Imaging side effects and complications of chemotherapy and radiation therapy: a pictorial review from head to toe

Abstract: Newer biologic drugs and immunomodulatory agents, as well as more tolerated and effective radiation therapy schemes, have reduced treatment toxicity in oncology patients. However, although imaging assessment of tumor response is adapting to atypical responses like tumor flare, expected changes and complications of chemo/radiotherapy are still routinely encountered in post-treatment imaging examinations. Radiologists must be aware of old and newer therapeutic options and related side effects or complications to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 111 publications
1
30
0
Order By: Relevance
“…This finding goes in line with Albano, et al, (2021) who studied "Imaging side effects and complications of chemotherapy and radiation therapy" supports the opinion by stating that radiation therapy though administered locally, can produce systemic side effects such as fatigue, anorexia, nausea, vomiting, alteration in the taste, sleep disturbance, headache, anemia, dry skin, constipation etc. Also, this is consistent with Rajesh,, et al, (2022) who studied "An observational study to monitor and report radiation-related adverse events by a clinical pharmacist to achieve a better therapeutic outcome and suggest preventive measures in a tertiary care teaching hospital" reported that radiotherapy-induced fatigue was a common early and chronic side effect of irradiation and it was reported more in patients with head-and-neck cancers due to activation of Pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This finding goes in line with Albano, et al, (2021) who studied "Imaging side effects and complications of chemotherapy and radiation therapy" supports the opinion by stating that radiation therapy though administered locally, can produce systemic side effects such as fatigue, anorexia, nausea, vomiting, alteration in the taste, sleep disturbance, headache, anemia, dry skin, constipation etc. Also, this is consistent with Rajesh,, et al, (2022) who studied "An observational study to monitor and report radiation-related adverse events by a clinical pharmacist to achieve a better therapeutic outcome and suggest preventive measures in a tertiary care teaching hospital" reported that radiotherapy-induced fatigue was a common early and chronic side effect of irradiation and it was reported more in patients with head-and-neck cancers due to activation of Pro-inflammatory cytokines.…”
Section: Discussionsupporting
confidence: 80%
“…Part I: Socio-demographic characteristics of the studied patients. Table (1) shows that the highest percent of studied patients age (33.5%) was 60 years or more and (31.5%) falls between (50-<60), more than half of them were female patients (58,3%), Regarding educational level about (31.7%) of studied patients read and write, (38.3%) of studied patients are not working and (35%) are working, (66.7%) of studied patients have low income.…”
Section: Resultsmentioning
confidence: 99%
“…Functional MR data provide quantifiable information about underlying tissue characteristics [ 44 , 64 ]. The combination of objective biomarkers with morphologic data makes functional MRI a powerful tool that provides comprehensive information about lesion heterogeneity and therapy-induced changes in heterogeneity [ 28 , 85 , 86 ]. Functional MRI has additional potential in the early stages of treatment efficacy evaluation and should be useful in drug development [ 86 ].…”
Section: Functional Magnetic Resonance Imagingmentioning
confidence: 99%
“…Treatment for lung cancer differs according to subtype and stage ( Hayashi et al, 2011 ). Chemotherapy and radiotherapy have side effects ( Albano et al, 2021 ), and even targeted immunotherapeutic have a considerable symptom burden ( Lim et al, 2020 ). Therefore, research on new drugs and combined therapies is needed.…”
Section: Introductionmentioning
confidence: 99%